2014
DOI: 10.1111/ics.12158
|View full text |Cite
|
Sign up to set email alerts
|

Phytolatex synthesized gold nanoparticles as novel agent to enhance sun protection factor of commercial sunscreens

Abstract: Phytolatex synthesized gold nanoparticle is novel agent to enhance sun protection factor of commercial sunscreens. Gold nanoparticles aggregation in commercial sunscreen was the main factor behind SPF enhancement. This study showed that gold nanoparticles are potent alternative to traditionally used hazardous titanium dioxide and zinc oxide nanoparticles in sunscreen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…A ruby‐red Au NPs suspension was obtained after mixing HAuCl 4 for 5 min with the latex solution. In other studies, this colour change was also observed when gold chloride solution was mixed with latex [27, 50]. The results showed that absorbance progressively increased as reduction time increased, leading to a plateau or saturation at 120 min (Fig.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…A ruby‐red Au NPs suspension was obtained after mixing HAuCl 4 for 5 min with the latex solution. In other studies, this colour change was also observed when gold chloride solution was mixed with latex [27, 50]. The results showed that absorbance progressively increased as reduction time increased, leading to a plateau or saturation at 120 min (Fig.…”
Section: Resultssupporting
confidence: 71%
“…Das et al (2011) [29] reported that aqueous extracts of Calotropis procera latex require 20 min to efficiently reduce HAuCl 4 (1.0 mmol/L) to Au NPs. Borase et al (2014) [27] observed that the absorbance of Au NPs colloid synthesised using latex from Jatropha gossypiifolia increased as incubation time increased.…”
Section: Effect Of Reduction Timementioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Green synthesized AuNPs can also exhibit anticancer and antimicrobial activity, 16 antioxidant moisture retention, skin lightening properties, 17 and sunscreen ability, enlarging their applicability. 18,19 As reported by Gonnelli et al, 20 synthetic routes relying on green chemistry show other advantages for large scale production adopting mild conditions of work. 20 For green synthesized AuNPs, additional assembling steps are not necessary since the AuNP properties are ascribed to the main components present on their surface and used to induce their formation.…”
Section: Introductionmentioning
confidence: 96%
“…In vitro spectrophotometric method was used for SPF determination (Dutra et al, 2004;Borase et al, 2014). In brief, commercially available sunscreen with labelled SPF of 15 was constituted as control respectively while, test contains the above commercial sunscreens spiked with PCA at concentration of 0.1, 0.2 and 0.4 % w/w of sunscreen.…”
Section: In Vitro Determination Of Uvb Protection By Sun Protection Factor (Spf)mentioning
confidence: 99%